A study of geomagnetic field time variations over southern Africa using a regional harmonic spline core magnetic field model derived from CHAMP satellite and ground magnetic observations - Nahayo, Emmanuel (My University, 2019)
The geomagnetic field spatial variation in Southern Africa is characterised by a high horizontal gradient, and its study requires high spatial resolution data. Regional field models are more suitable than global models to study small scale features of the geomagnetic field variation. They use more dense data, hence a good data coverage allows a detailed description of the geomagnetic variation in the area of investigation. In Southern Africa, the ground recording stations are limited (4 magnetic observatories and 38 geomagnetic repeat stations) and satellite data are needed for studies where high spatial and temporal resolution data are required. The southern African region borders the South Atlantic Anomaly (SAA) where the strength of the magnetic field is approximately 30% weaker compared to other regions of the same latitudes. In an attempt of supporting geomagnetic field model data users and investigating the evolution of the South Atlantic Anomaly, a study to develop and derive a southern African regional field model combining CHAMP satellite data with ground-based data showed that the regional model over Southern Africa can be improved by combining both satellite and ground-based data. The internal Earth processes generating the main field can be studied by modelling the core field using inversion of geomagnetic field components measured above the surface of the Earth, and they assist in monitoring the long-term variation of the geomagnetic field on time scales of 1 year and more, therefore giving valuable information on the evolution of the SAA in southern Africa. The study of the geomagnetic field time variation in the southern Africa region was carried out applying the harmonic splines technique on CHAMP satellite and ground data that have been recorded between 2001 and 2010. A Southern Africa Regional Model (SARM) was derived and evaluated using global models, such as International Geomagnetic Reference Field (IGRF-11) and GFZ Reference Internal Magnetic Model (GRIMM), by calculating the difference between SARM and global models. The results of this study suggest that the 200 km gridded SARM model developed from only satellite data is shown to match monthly averaged ground data to within 1.5%, 1.6% and 0.7% for X, Y and Z, respectively, suggesting the temporal variations are valid where ground data are not available. In addition, these results also confirm the earlier findings of the 2007 magnetic jerk and rapid secular variation fluctuations of 2003 and 2004 on the eastern edge of the SAA which extends 1000 km into South Africa. CHAMP satellite and relatively densely spaced (300 km) ground-based data measured over southern African region between 2005 and 2010 are incorporated in a new regional, harmonic spline based, core field model. Our new SACFM-2 model is compared to our previously developed SARM model, a regional model based only on satellite data, and the global CHAOS-6 model developed by Finlay et al. (2016). The results agree well with the CHAOS-6 model (within 0.4%) in the vertical (Z) component and total field (F) that are used to investigate the evolution of the South Atlantic Anomaly in the region. The computed maps of main field of the Z component and total intensity F show a steady decrease of the field between 2005.5 and 2010.5, reaching an average of 40 nT and 50 nT per year, respectively, in the southwest of South Africa, indicating evolution of the South Atlantic Anomaly under Southern Africa and an increase of the geographical area of this feature. In addition, a southern African lithospheric magnetic model (SALMM) over Southern Africa was developed based on the Spherical Cap Harmonic Analysis method using CHAMP satellite measurements at an altitude between 332 km and 365 km, and between 2007.0 and 2009.0 epochs. This lithospheric magnetic model SALMM was compared to a regional model developed by Vervelidou et al. (2018) and the global model MF7. Our lithospheric magnetic model SALMM was interpreted in terms of regional (100s km) geological features and long-wavelength geological magnetic anomalies.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment for the degree of Doctor of Philosophy Johannesburg, October 2019
Keywords: Geomagnetism; Geophysics; Geology--South Africa